KAJIAN HUKUM JAMINAN HAK TANGGUNGAN YANG DILELANG TANPA PROSES PERMOHONAN LELANG EKSEKUSI KE KETUA PENGADILAN NEGERI - Catur Budi Dianawati; Amin Purnawan (Jurnal Akta, 2017)
The facts on the field showed that the creditors often conducted public auction without first applying to the Chairman of the District Court, yet directly to the auction office made under article 6 of law number 4 year 1996 about mortgage right upon land and things related to it. The following were the problem formulation of the study; (1) how should the procedure for public auction be made according on the law number 4 year 1996 about mortgage right upon the land and things related to it? (2) Why did the creditors auction the guarantee of the dependent right without experiencing the process of proposing the permit for the auction to the Chairman of the District Court? (3) What would the legal consequences be towards the guarantee of the mortgage right auctioned without the process of getting the permit from the Chairman of the District Court?Method used in this study was adopted from the approach of juridical empirics (empirical legal research). The collected data were processed and verified using descriptive analysis to which it is frequently intended to research for human, condition and other phenomena.Based on the result in this study and the result from discussion about the procedure of public auction towards the guarantee of mortgage rights according to the law Number 4 Year 1996 about mortgage rights upon land and things related to it to which it is arranged in the provision of article 26. It is observed that as long as there is no rules of legislation specifically governs the execution of mortgage rights, the procedure of this execution should comply with hypothec execution as arranged in article 224 in the refurbished Indonesia Regulation (Het Herziene Indonesisch Reglement/HIR). Article 6 of the law Number 4 Year 1996 about mortgage right upon land and things related to it where it gives the right to the creditors holding the first mortgage right to sell the object on his own power, in case, the debtors violates the commitment, became the reasons why they auctioned the guarantee of the right without proposing the permit for the auction to the Chairman of the District Court. The legal consequence towards the guarantee of the mortgage right auctioned without experiencing the process of proposing the permit for the auction to the Chairman of the District Court was null and void. Keywords         : Guarantee of Mortgage Right, Public Auction, Chairman of District Court